ANALISIS FAKTOR YANG MEMPENGARUHI KESULITAN GURU DALAM PENGGUNAAN MODUL AJAR - Ihsan Syah Putra; Charenina Tsabitha Amanda; Sri Harmuli; Novitasari; Sintia Hepi Andini; Nawang Anggi; Khoirunnisa; Muhammad Sofwan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the factors that influence teachers' difficulties in using teaching modules as learning tools that support the Independent Curriculum. Teaching modules are an important part of the implementation of independent and differentiated learning, but many teachers face obstacles in their use. This study uses a descriptive qualitative approach involving 15 teachers from elementary school levels spread across three schools in Kerinci Regency. Data were collected through in-depth interviews, classroom observations, and documentation studies. The results of the study indicate that teachers' difficulties in using teaching modules are influenced by several factors, namely (1) limited understanding of the structure of teaching modules, (2) low digital skills to access and modify modules, (3) limited time to adjust modules to student needs, and (4) lack of adequate technical training. This study recommends increasing training support, providing contextual and flexible modules, and collaboration between teachers in learning communities to reduce these obstacles.